Cost estimates of the Kigali Amendment to phase-down hydrofluorocarbons. Issue 75 (September 2017) - Höglund-Isaksson, Lena; Purohit, Pallav; Amann, Markus; Bertok, Imrich; Rafaj, Peter; Schöpp, Wolfgang; Borken-Kleefeld, Jens
Highlights: Kigali Amendment compliance removes 39 Pg CO2 eq or 61% of global pre-Kigali baseline HFC emissions in 2018 to 2050. The sector composition of the future demand for cooling services has important implications for abatement costs. All four Party groups have large initial opportunities to reduce emissions at low costs or even at net profits. Around 2040 abatement costs are expected to start increasing, in particular in Article 5 countries. Kigali Amendment compliance means possible electricity savings of about 0.7% of expected global electricity consumption in 2018 to 2050. Abstract: Hydrofluorocarbons (HFCs) are synthetically produced compounds primarily used for cooling purposes and with strong global warming properties. In this paper, we analyze the global abatement costs for achieving the substantial reductions in HFC consumption agreed in the Kigali Amendment (KA) of the Montreal Protocol from October 2016. We estimate that compliance with the KA is expected to remove 39 Pg CO2 eq or 61% of global baseline HFC emissions over the entire period 2018–2050. The marginal cost of meeting the KA targets is expected to remain below 60 €/t CO2 eq throughout the period in all world regions except for developed regions where legislation to control HFC emissions has already been in place since a few years. For the latter regions, the required HFC consumption reduction is expected to come at a marginal cost increasing steadily to between 90 and 118 €/t CO2 eq in 2050. Depending on the expected rate of technological development and the extent to which envisaged electricity savings can be realized, compliance with KA is estimated attainable at a global cost ranging from a net cost-saving of 240 billion € to a net cost of 350 billion € over the entire period 2018 to 2050 and with future global electricity-savings estimated at between 0.2% and 0.7% of expected future electricity consumption.